How to defend your lair - Ammann, Keith (The monsters know what they're doing, 2022)
"The world is a dangerous place--especially when you're up to no good. Whether you're a rampaging monster, a calculating mastermind, or the current possessor of the Golden MacGuffin, someone's going to come at you. Probably more than one someone. You can't know when, but you can choose where. You need to be ready. You need a lair. In How to Defend Your Lair, gamemaster Keith Ammann pulls back the curtain on an underrated but crucial part of any tabletop roleplaying game: the theater of battle. Say goodbye to encounters in randomly generated dungeons and hello to a game in which where the fight takes place is just as important as who is doing the fighting. This book teaches you how to use real-world principles of building security and area defense to create strongholds infused with flavor, informed by narrative, and complex enough to force your players to think strategically. You'll look at the strengths and weaknesses of both defenders and potential attackers, creating spaces that are strong enough to keep out ordinary intruders...and to provide thrilling challenges to extraordinary ones."-- Page 2 of cover.